Poly(ethylene glycol) hydrogels with cell cleavable groups for autonomous cell delivery. (January 2016) - Kar, Mrityunjoy; Vernon Shih, Yu-Ru; Velez, Daniel Ortiz; Cabrales, Pedro; Varghese, Shyni
Abstract: Cell-responsive hydrogels hold tremendous potential as cell delivery devices in regenerative medicine. In this study, we developed a hydrogel-based cell delivery vehicle, in which the encapsulated cell cargo control its own release from the vehicle in a protease-independent manner. Specifically, we have synthesized a modified poly(ethylene glycol) (PEG) hydrogel that undergoes degradation responding to cell-secreted molecules by incorporating disulfide moieties onto the backbone of the hydrogel precursor. Our results show the disulfide-modified PEG hydrogels disintegrate seamlessly into solution in presence of cells without any external stimuli. The rate of hydrogel degradation, which ranges from hours to months, is found to be dependent upon the type of encapsulated cells, cell number, and fraction of disulfide moieties present in the hydrogel backbone. The differentiation potential of human mesenchymal stem cells released from the hydrogels is maintained in vitro . The in vivo analysis of these cell-laden hydrogels, through a dorsal window chamber and intramuscular implantation, demonstrated autonomous release of cells to the host environment. The hydrogel-mediated implantation of cells resulted in higher cell retention within the host tissue when compared to that without a biomaterial support. Biomaterials that function as a shield to protect cell cargos and assist their delivery in response to signals from the encapsulated cells could have a wide utility in cell transplantation and could improve the therapeutic outcomes of cell-based therapies.